Analysis of Innovation in Medical Tourism in the Zachodniopomorskie Region - Biernacka , Joanna (Studia Oeconomica Posnaniensia, 2014)
This paper discusses the subject of innovation in medical tourism services. It defines the concept of medical tourism and positions it as one of the forms of health tourism. The paper presents the general concept as well as the importance of innovation in tourism services, especially in the context of medical tourism. It contains a detailed analysis of innovation in medical tourism covering the Zachodniopomorskie region as this is the leading area for such services in Poland. The influence of medical tourism on the development of the region is also examined.